Patients' perspectives about the design of a mobile application for psychotic disorders - Simões de Almeida, Raquel (2021)
Based on the design of applications for psychotic disorders illness self-management, this study aimed to understand patients’ patterns of technology usage, as well as their expectations and requirements concerning the design of an app for rehabilitation and illness management purposes. It also aimed to identify guidelines for mobile application development for this population.